Iconic stories. From the History of images to images-history - Bouhaben, Miguel Alfonso; Martín Hernández, Rut (Anales de Historia del Arte, 2024)
The general objective of the research is to analyze the main strategies of pictorial practices that make up iconic stories to establish a typology of images that allows us to understand their peculiarities. A mixed methodology has been implemented. On the one hand, a qualitative analysis of artistic practices and the conceptual typologies that derive from them. At a first level, an approach to the historical-linear evolution of the structural relationships that are established between the multiplicity of images. To this end, a typology of the ways of relating with images has been built throughout the History of pictorial images: the fold-image, the deconstruction-image, the series-image, the sequence-image and the assembly-image. . At a second level, a non-linear approach to the ways of incorporating the gaze, the body and the biographical into the processes of story configuration. In this case, a typology of the ways of telling with images in the contemporary context has been configured: the image-story, the image-story, the image-archive and the image-(dis)appeared. On the other hand, an investigation in the arts based on an iconic story that is presented intertwined with the textual part of the article, on the same plane of epistemic equality.
Keywords: iconic story; image typologies; pictorial proposals; multiplicity; history